Prospects of Statins in Parkinson Disease - Roy, Avik (2011)
Parkinson disease (PD) is second only to Alzheimer disease as the most common neurodegenerative disorder in humans. Despite intense investigations, no effective therapy is available to halt the progression of PD. Although statins are widely used cholesterol-lowering drugs throughout the world, recent studies suggest that these drugs modulate neurodegeneration-related signaling processes and may be beneficial for PD. Simvastatin is the most potent statin in crossing the blood-brain barrier, and this particular statin drug negatively correlates with the incidence of PD and shows efficacy in animal models of PD. However, PD mainly occurs in the aging population, who are more vulnerable to cholesterol or lipid-related disorders, raising questions whether this possible beneficial effect of statins in PD patients is cholesterol dependent or cholesterol independent. This article presents data on the therapeutic efficacy of simvastatin in a chronic MPTP model of PD, reviews recent literature, and discusses the pros and cons of statin therapy in PD.